Scattering of the field of an electric dipole by a conic structure with longitudinal slots - Doroshenko, V. A.; Kravchenko, V. F. (IEEE, 2000)
The excitation of a semi-infinite perfectly conducting infinitely thin circular cone with semi-infinite slots by a radial electric dipole is investigated. The slots are cut along the cone generatrices and equally spaced. The problem is solved based on the Kontorovich-Lebedev integral transform and the Riemann-Hilbert problem method. Analytic solutions are obtained for a semitransparent cone and a cone with narrow slots. The effect of slots on the field structure, polarization, and behavior in the proximity of the cone vertex is studied.
Keywords: radial electric dipole; Kontorovich-Lebedev integral transform; Riemann-Hilbert problem method